Measurement in jejunal biopsies by computer-aided microscopy. Issue 3 (March 1980) - Slavin, G; Sowter, C; Robertson, K; McDermott, S; Paton, K
Abstract : A method of morphometric analysis of jejunal mucosa using computer-aided microscopy is described. It is based on the technique of interactive computer graphics with definition by the observer of areas and lengths for measurement, but it also includes automatic measurements based on grey-level segmentation. The analyses are performed rapidly and efficiently. The technique is applicable to the analysis of biopsy tissue from many sites.